Small-scale Farming and Access to Market: Challenges and Opportunities in South Africa - Confidence Ndlovu; Mandla Masuku (Borong Newinera Publisher, 2021)
The paper has aimed to explore the effectiveness of small-scale farmers in improving household income and food security, particularly looking at the barriers to market access in rural areas. This study was undertaken in rural areas of Kanyamazane, Clau-Clau and Nyongane, South Africa, where small-scale producers depend on low-risk and low-return markets to generate household income from production, thus ensuring food security. To achieve the aim of this study, a qualitative approach was used to provide in-depth interpretation of the perspectives, experiences, and behavioural patterns of the small-scale farmers faced with market related issues. Small-scale farmers, agricultural extension officers, and municipal officials were purposefully selected to share their views, perceptions, and experiences on the effectiveness in accessing markets. The findings revealed that there was limited access to formal markets by small-scale farmers because of limited knowledge and capacity to meet market requirements. The study confirmed that a lack of marketing skills, institutional support services, and limited access to arable land, have directly negative effects on achieving livelihood outcomes. This study recommends a sustainable crop production method which reduces the costs of farming resources, such as pesticide and fertilizer, through organic methods to ensure food safety and enhanced nutrient quality. This study further encourages inclusive rural development, where small-scale producers are treated as stakeholders in agricultural policy formulation to enable access to financial resources and increase in production through the formation of cooperatives.